Resource-Depleted Quarries Adaptive Re-Use for Sustainable Redevelopment & Land Reclamation (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
A quarry is an area from which rocks such as marble, limestone, and granite are extracted for industrial use. Once depleted of their desired resources, quarries are frequently abandoned. The resulting gaping holes can fill with water and form dangerous quarry lakes while others are turned into unsightly landfills. When quarries are in close proximity to urban environments, inhabitants are subjected to pollution and noise, and the undeniable eyesore of an abandoned quarry remains long after excavation is completed. Sustainable redevelopment has become a shining solution for these abandoned, resource depleted quarries. Dozens of cities have undertaken adaptive re-use projects to transform quarries into a variety of public and private spaces. The potential new uses for these expanses of land include sites for research and education, aquaculture, recreational activities, storage, industry and housing.Not only do quarries often negatively impact those who live nearby, but they often leave residual negative impacts on the environment. Runoff of chemical pollutants into bodies of water, loss of natural habitats, farmland, and vegetation, and natural resource exhaustion are among the most harmful environmental impacts.While quarrying can be a negative industry for society and for the environment, the necessity of quarrying is undeniable. In order for human civilization to continue as it has since the industrial revolution, we need the retrieval of resources from quarries in order to create our homes foundations, transportation structures with cement, concrete, asphalt, and crushed stone, and other industrial uses such as abrasives, binders, additives, and roofing. Millions of people worldwide are employed by quarrying practices, and therefore a removal of the quarrying industry would result in the loss of jobs for countless families. Therefore, in order to remedy the negative effects of quarrying, we must use the resource depleted spaces for other practices once the quarries cease being operational. The potential transformation of quarry sites into a variety of sustainable uses would not only remedy the negative effects of quarrying, but could create sites of greater social, environmental value.The goal of this research is to encourage the rehabilitation of land disturbed by quarrying by making the areas suitable for new sustainable land uses.